Positive psychology for addiction : theory, research and application - Ogilvie, Lisa; Carson, Jerome (Positive psychology in practice, 2025)
In addiction recovery, fostering a positive life that enhances satisfaction, well-being, and personal capability is crucial for long-term success. By staying motivated and actively engaging in their recovery, individuals can significantly elevate their quality of life. This groundbreaking work unveils the transformative potential of positive psychology in addiction recovery, highlighting how cultivating positivity and resilience can lead to profound and lasting improvements. Exploring the theoretical foundations of positive psychology and its application to mental health, Ogilvie and Carson focus particularly on how overcoming adversity can lead to positive outcomes. They delve into second wave positive psychology's perspective on resilience and third wave's pluralistic approach, integrating insights from the recovery model of mental health, well-being studies, the process of change, and asset-based recovery frameworks. With detailed examples of recent studies and practical guidance for practitioners, Positive Psychology for Addiction offers a comprehensive and holistic view of addiction recovery and challenges traditional deficit-focused approaches by advocating for strengths-based recovery methods. Demonstrating the synergy between positive psychology and effective addiction recovery, Positive Psychology for Addiction provides a valuable resource that promotes a positive lifestyle choice and contributes to reducing the stigma surrounding addiction. This important work is essential for anyone involved in addiction recovery, from clinical practitioners to academics and individuals in recovery.